QT interval prolongation in people treated with bedaquiline for drug-resistant tuberculosis - Rayhan, Mohammad Zannatul; Sadi, M. Rokib; Sarker, Prosad Kumer; Hossain, M. Asif; Alam, Most Mehenaz (International Journal of Research in Medical Sciences, 2024)
Background: Bedaquiline (BDQ) is indeed recommended for treating multidrug-resistant tuberculosis (MDR-TB). However, it's essential to monitor patients receiving bedaquiline therapy closely because it has been associated with prolongation of the QTc interval. This study aimed to assess the association of bedaquiline to QT interval prolongation in DR-TB patients. Methods: This was an observational longitudinal study conducted in the Department of Respiratory Medicine in Chest Disease Hospital, Rajshahi, from August 2020 to February 2023. A total of 44 MDR-TB patients were included in the study. Data analyses were done by using Statistical Package for Social Sciences (SPSS) version 25.0. Results: Out of 44 patients the majority 30(68.2%) patients belonged to age >40 years with a mean age of 49.3±15.6 years, and all patients were male. All MDR patients were detected by sputum Gene-Xpert, 44 (100%), and sputum for AFB culture was done in all patients, 44 (100%). QT level and QT changes were statistically significant for baseline and 24 weeks. Only one patient died in 2 weeks of follow-up (Table 3). Changes of QT >60 ms was found in 6 (13.6%) and ≤60 ms was 38 (86.4%). Age, sex, marital status, residence, educational status, occupational status, monthly income, chief complaints, co-morbidities, and using drug-causing QT prolongation were not statistically significant (p>0.05). Conclusions: Prolonged QT interval is in DR-TB patients who receive treatment using the bedaquiline regimen. We observed that with a moderate prolongation of QTc, there were no arrhythmias recorded and 1 death occurred due to acute MI.